2019
DOI: 10.1111/den.13428
|View full text |Cite
|
Sign up to set email alerts
|

Lumen‐apposing metal stents for endoscopic ultrasonography‐guided interventions

Abstract: Lumen‐apposing metal stents (LAMS) are integrated in a single‐step delivery platform and can be deployed under endoscopic ultrasound‐guidance for the drainage of intra‐abdominal fluid collections, decompression of obstructed ductal systems, establishment of anastomosis or creation of fistulous tracts between organs that can facilitate further endoscopic interventions if required. A unique feature of LAMS is their ability to approximate the adjoining structures, thereby minimizing the potential for leak and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…It is now attributed to have effective roles in pancreatic cyst drainage, biliary drainage, and gastrojejunostomy. 30 The structure of this stent is characterized by a fully covered dumbbell-shaped short stent made up of braided nitinol wire, which makes it possible to prevent tract leakage, migration, and tissue ingrowth and allows removability and trans-stent interventional procedures. Will et al reported a case of EUS-PTS using LAMS (AXIOS; Boston Scientific) for a patient with recurrent episodes of severe chronic pancreatitis and retention of fluid in the PD against a background of pancreatolithiasis with ERCP failure.…”
Section: Technical Tips For Stent Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now attributed to have effective roles in pancreatic cyst drainage, biliary drainage, and gastrojejunostomy. 30 The structure of this stent is characterized by a fully covered dumbbell-shaped short stent made up of braided nitinol wire, which makes it possible to prevent tract leakage, migration, and tissue ingrowth and allows removability and trans-stent interventional procedures. Will et al reported a case of EUS-PTS using LAMS (AXIOS; Boston Scientific) for a patient with recurrent episodes of severe chronic pancreatitis and retention of fluid in the PD against a background of pancreatolithiasis with ERCP failure.…”
Section: Technical Tips For Stent Deploymentmentioning
confidence: 99%
“…The indications for a lumen-apposing metal stent (LAMS), which was originally designed to provide solid anchorage between nonadherent luminal structures, have widened. It is now attributed to have effective roles in pancreatic cyst drainage, biliary drainage, and gastrojejunostomy [ 30 ]. The structure of this stent is characterized by a fully covered dumbbell-shaped short stent made up of braided nitinol wire, which makes it possible to prevent tract leakage, migration, and tissue ingrowth and allows removability and trans-stent interventional procedures.…”
Section: Techniquesmentioning
confidence: 99%
“…gastroentorostomy, pancreatic fluid collection, gallbladder), but mainly with the use of the 10 × 10‐mm size and located in the gastric cavity. At the same time, a LAMS‐in‐LAMS technique, a new variant of the well‐known stent‐in‐stent technique, has recently been described in a few cases to remove the embedded covered metal stent 1‐5 …”
Section: Brief Explanationmentioning
confidence: 99%
“…The AXIOS stents (Boston Scientific Corporation, Natick, MA) is available with a cautery delivery system (EC-LAMS "HOT" AXIOS) or a noncautery delivery system ("COLD" AXIOS); the SPAXUS (Taewoong Medical, Gyeonggi-do, South Korea). The NAGI ( Taewoong Medical) and PLUMBER (MI Tech, Gyeonggi-do, South Korea) stents are fully covered SEMS with 2 antimigratory flanges that could be an options in EUS [34]. The diameter and length measurements vary between 6 mm £ 8 mm and 16 mm £ 30 mm.…”
Section: Lumen Apposing Metal Stentsmentioning
confidence: 99%